Distributed Control System Applied in Temperatur Control by Coordinating Multi-loop Controllers - Edi Rakhman; Feriyonika Feriyonika (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
In Distributed Control System (DCS), multitasking management has been important issues continuously researched and developed. In this paper, DCS was applied in global temperature control system by coordinating three Local Control Units (LCUs). To design LCU’s controller parameters, both analytical and experimental method were employed. In analytical method, the plants were firstly identified to get their transfer functions which were then used to derive control parameters based on desired response qualities. The experimental method (Ziegler-Nichols) was also applied due to practicable reason in real industrial plant (less mathematical analysis). To manage set-points distributed to all LCUs, master controller was subsequently designed based on zone of both error and set-point of global temperature controller. Confirmation experiments showed that when using control parameters from analytical method, the global temperature response could successfully follow the distributed set-points with 0% overshoot, 193.92 second rise time, and 266.88 second settling time. While using control parameters from experimental method, it could also follow the distributed set-points with presence of overshoot (16.9%), but has less rise time and settling time (111.36 and 138.72 second). In this research, the overshoot could be successfully decreased from 16.9 to 9.39 % by changing master control rule. This proposed method can be potentially applied in real industrial plant due to its simplicity in master control algorithm and presence of PID controller which has been generally included in today industrial equipments.